2012
DOI: 10.1001/archpediatrics.2011.748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pediatric Bilateral Cochlear Implantation on Language Development

Abstract: To examine spoken language outcomes in children undergoing bilateral cochlear implantation compared with matched peers undergoing unilateral implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
2
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 16 publications
7
109
2
3
Order By: Relevance
“…However, children implanted before the age of two perform significantly better on all three tests than children who were implanted at an older age (p < 0.001). Also, the bilaterally implanted children outperform the unilaterally implanted ones on receptive and expressive skills (Boons et al, 2012a). Still, even these children do not approach the age equivalent score.…”
Section: Spoken Languagementioning
confidence: 90%
“…However, children implanted before the age of two perform significantly better on all three tests than children who were implanted at an older age (p < 0.001). Also, the bilaterally implanted children outperform the unilaterally implanted ones on receptive and expressive skills (Boons et al, 2012a). Still, even these children do not approach the age equivalent score.…”
Section: Spoken Languagementioning
confidence: 90%
“…Open-set speech recognition scores correlate significantly with measures of speech production and language [Tait et al, 2010]. Several studies reported significant mutually related improvements in auditory, speech, and vocabulary development but not in the development of more complex language performance [Svirsky et al, 2004;Geers et al, 2008;Archbold, 2010;De Raeve, 2010;Sparreboom et al, 2010;Boons et al, 2012Boons et al, , 2013. The reason for the relatively favorable vocabulary development contrasted to the more delayed morphosyntactical and pragmatic development might be that vocabulary is often taught in an explicit manner to deaf children, but for hearing children, more than 80% of language and, 'general knowledge' is acquired in incidental learning situations [Gillis and Schaerlaekens, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of hearing, important benefits have been reported for sound localization and speech perception in noise [Van Deun et al, 2009]. The use of bilateral CIs was also associated with improved acquisition of complex language skills [Boons et al, 2012]. It should also be noted that several studies have shown a 'verbal achievement gap' between deaf students with a unilateral CI and normal-hearing students, which increased as the students progressed through school and language became more complex [Geers et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…[70] also used the CAP as outcome measure in a group of 35 children with bilateral CIs, showing that after three years of bilateral implant use, higher CAP scores were obtained for significantly more children than before their second implant. Although the positive effect of bilateral implantation on spoken language development has recently been demonstrated [45,53], the influence of bilateral implantation on speech production remains to be demonstrated [48].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of bilateral implantation in children are well documented in terms of improved localization [46][47][48] and enhanced speech recognition in quiet [49,50] and in noise [46,51,52] when compared to listening with a unilateral CI. Also recently confirmed, children with bilateral CIs have significantly better language outcomes compared to children with unilateral CIs [45,53]. However, there is still a lack of evidence regarding the effect of bilateral cochlear implantation on broader outcomes such as literacy, academic skills and overall quality of life, particularly concerning long-term outcomes [45,48,54].…”
Section: Introductionmentioning
confidence: 98%